2017
DOI: 10.3390/met7090373
|View full text |Cite
|
Sign up to set email alerts
|

Fretting Wear Behaviors of Aluminum Cable Steel Reinforced (ACSR) Conductors in High-Voltage Transmission Line

Abstract: This work reports the fretting wear behavior of aluminum cable steel reinforced (ACSR) conductors for use in high-voltage transmission line. Fretting wear tests of Al wires were conducted on a servo-controlled fatigue testing machine with self-made assistant apparatus, and their fretting process characteristics, friction force, wear damage, and wear surface morphology were detailed analyzed. The results show that the running regime of Al wires changes from a gross slip regime to a mixed regime more quickly as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In ACSR, the aluminum line and the galvanized steel core are in direct contact, and this structure is very prone to galvanic corrosion (Håkansson et al, 2015), which is also the main form of ACSR corrosion. At the same time, mechanical wear also accelerates ASCR corrosion, and the fretting wear caused by the aeolian vibration and galloping of the conductor will lead to plastic deformation, wear, and cracking, and eventually fatigue failure (Ma et al, 2017). For transmission lines operating in coastal areas, the combined effects of salt spray corrosion and fretting wear can increase the severity of ASCR corrosion.…”
Section: Coatings Aim At Conductors Corrosionmentioning
confidence: 99%
“…In ACSR, the aluminum line and the galvanized steel core are in direct contact, and this structure is very prone to galvanic corrosion (Håkansson et al, 2015), which is also the main form of ACSR corrosion. At the same time, mechanical wear also accelerates ASCR corrosion, and the fretting wear caused by the aeolian vibration and galloping of the conductor will lead to plastic deformation, wear, and cracking, and eventually fatigue failure (Ma et al, 2017). For transmission lines operating in coastal areas, the combined effects of salt spray corrosion and fretting wear can increase the severity of ASCR corrosion.…”
Section: Coatings Aim At Conductors Corrosionmentioning
confidence: 99%
“…With high-voltage (HV) overhead lines (OHLs) facing an increasingly complex and deteriorating service environment, corrosion and wear damages are two of the main areas of OHL failures [3]. Aluminium and its alloys not only have the advantage of light weight, but also have good conductivity and excellent corrosion resistance, making them one of the most commonly used overhead conductor materials [4], [5]. However, due to the poor mechanical properties and wear resistance of aluminium and its lack of stability at high temperatures, surfaces made of the aluminium oxide are more prone to damage, eventually resulting in corrosion protection failures [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…The authors revealed that adhesion/abrasive fretting damage mechanisms were dominant in aluminum wires. Ma et al [45] studied the wear performance of ACSR in different environments, revealing that the primary wear mechanisms change from abrasive/adhesive wear to abrasive wear/fatigue damage in dry friction environments and NaCl solution.…”
Section: Introductionmentioning
confidence: 99%